THE CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND SPEAKING ACHIEVEMENT OF EIGHT GRADE STUDENTS OF SMP N 46 PALEMBANG, SOUTH SUMATERA, INDONESIA - Manalulallaili Manalulallaili; Amala Hasanah; Herizal Herizal; Agnes Silvita (JAMBI-ENGLISH LANGUAGE TEACHING, 2018)
This study investigated the correlation between students’ emotional intelligence to their speaking achievement and the significant influence between students’ emotional intelligence to their speaking achievement. The population of were 294 students of eight grade students of SMP N 46 Palembang, South Sumatera, Indonesia in the academic year 2016/2017. We used cluster random sampling to determine the sample of this study. There were 74 students as a sample of this study. A quantitative study was used in this study. The data were obtained by questionnaires and speaking test. The result of the test was analyzed by means and percentage. Based on the result of the data analysis, there were two major findings. First, there was significant correlation between students’ emotional intelligence and their speaking achievement and second is students’ emotional intelligence did significant influence 3,11% to their speaking achievement.